2015
DOI: 10.1242/dev.116657
|View full text |Cite
|
Sign up to set email alerts
|

Striatal astrocytes produce neuroblasts in an excitotoxic model of Huntington's disease

Abstract: In the adult brain, subsets of astrocytic cells residing in well-defined neurogenic niches constitutively generate neurons throughout life. Brain lesions can stimulate neurogenesis in otherwise non-neurogenic regions, but whether local astrocytic cells generate neurons in these conditions is unresolved. Here, through genetic and viral lineage tracing in mice, we demonstrate that striatal astrocytes become neurogenic following an acute excitotoxic lesion. Similar to astrocytes of adult germinal niches, these ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 42 publications
5
114
0
Order By: Relevance
“…But we and others have recently found that parenchymal astrocytes residing in the striatum can also generate neurons (Magnusson et al, 2014;Nato et al, 2015;Luzzati et al, 2014;Duan et al, 2015;Shen et al, 2015). These striatal astrocytes are triggered by certain injuries, such as stroke, to activate latent neurogenic properties and produce neurons in a burst of proliferation (Fig.…”
Section: Striatummentioning
confidence: 96%
See 3 more Smart Citations
“…But we and others have recently found that parenchymal astrocytes residing in the striatum can also generate neurons (Magnusson et al, 2014;Nato et al, 2015;Luzzati et al, 2014;Duan et al, 2015;Shen et al, 2015). These striatal astrocytes are triggered by certain injuries, such as stroke, to activate latent neurogenic properties and produce neurons in a burst of proliferation (Fig.…”
Section: Striatummentioning
confidence: 96%
“…3). As mentioned, the similarities between parenchymal astrocytes and neural stem cells even extend to an intrinsic capacity of parenchymal astrocytes to generate neurons, at least when it comes to striatal astrocytes in vivo (Magnusson et al, 2014;Nato et al, 2015;Duan et al, 2015;Luzzati et al, 2014) and cortical astrocytes when isolated and cultured in vitro (Buffo et al, 2008;Shimada et al, 2012;Sirko et al, 2013). But the relatedness between the two cell types might go even further than that.…”
Section: Regional Differences In the Astrocyte Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…Its deletion might be sufficient to convert a substantial number of adult hippocampal neuroblasts to become oligodendrocytes without the concurrent cell death that occurs upon Nfix deletion. There is precedent for similar cell-type conversions between disparate cell types, for example it was recently shown that adult striatal astrocytes exhibit a latent neurogenic program that is actively suppressed via Notch signalling (Magnusson et al, 2014) and elicited by injury (Nato et al, 2015).…”
Section: Discussionmentioning
confidence: 99%